Literature Survey Of Protein Secondary Structure Prediction - Vel Arjunan, Satya Nanda; Deris, Safaai; Md. Illias, Md. Illias (Penerbit UTM Press, 2001)
In the wake of large-scale DNA sequencing projects, accurate tools are needed to predict protein structures. The problem of predicting protein structure from DNA sequence remains fundamentally unsolved even after more than three decades of intensive research. In this paper, fundamental theory of the protein structure of the protein structure will be presented as a general guide to protein secondary structure prediction research. An overview of the state-of-theart in sequence analysis and some princi ples of the methods invloved wil be described.